Susceptibility-guided therapy for Helicobacter pylori infection treatment failures. (September 2019) - Yu, Lou; Luo, Laisheng; Long, Xiaohua; Liang, Xiao; Ji, Yingjie; Chen, Qi; Song, Yanyan; Li, Xiaobo; Graham, David Y.; Lu, Hong
Background: Empirical therapy of Helicobacter pylori frequently results in treatment failure due to unrecognized antimicrobial resistance. The aim of this study was to investigate the effectiveness of susceptibility-guided therapy for rescue treatment of H. pylori infection in China. Methods: This was a prospective study of consecutive 200 patients infected with H. pylori with one or more treatment failures. The therapy chosen was susceptibility based using the most effective, best-tolerated regimens first and a locally proven, reliably effective regimen for multidrug-resistant infections. All patients received 14-day triple therapy, i.e. esomeprazole 20 mg and amoxicillin 1 g twice a day plus clarithromycin 500 mg twice a day, metronidazole 400 mg twice a day, or levofloxacin 500 mg daily, or, for multidrug-resistant infections, amoxicillin-containing bismuth quadruple therapy with esomeprazole 20 mg twice a day, bismuth 220 mg twice a day, amoxicillin 1 g three times a day, and metronidazole 400 mg four times a day. Antibiotic resistance was determined by agar dilution. Results: The eradication rate of susceptibility-guided therapy overall was 94.5% (189/200, 95% confidence interval: 90.4–97.2%). Around 28% (56/200) of patients carried strains susceptible to one of the tested antibiotics and were prescribed the triple therapy. A total of 144 multidrug-resistant patients received bismuth quadruple therapy. The eradication rates were all greater than 90%, i.e. 91.7% (11/12), 92.3% (12/13), and 93.5% (29/31) in those who received clarithromycin, metronidazole, and levofloxacin-containing triple therapy and 95.1% (137/144) for the bismuth quadruple therapy. There were no differences in eradication rates between the subgroups. Conclusions: Although susceptibility-guided therapy proved high efficacious despite the high proportion of multidrug-resistant strains, the strategy suggested the best approach for this population would be empirical amoxicillin-containing bismuth quadruple therapy.ClinicalTrials.gov identifier: NCT03413020.